2007
DOI: 10.1111/j.1745-7254.2007.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of polypeptide from Chlamys farreri protecting HaCaT cells from apoptosis induced by UVA plus UVB

Abstract: Aim: To investigate the mechanism of polypeptide from Chlamys farreri (PCF) protecting HaCaT cells from apoptosis induced by UVA plus UVB in vitro. Methods: An apoptotic model of UV irradiation-induced HaCaT cells was established. The 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide assay, agarose gel electrophoresis, biochemical methods, and Western blotting were employed in the study. Results: PCF inhibited the UV irradiation-induced apoptosis of HaCaT cells. PCF strongly reduced the intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…In this study, we confirmed that PCF could protect HaCaT cells from UVB-induced apoptosis, which is consistent with our previous findings [9]. Furthermore, we investigated iNOS and TGF-b1 as molecular mechanism of UVBinduced apoptosis cells and PCF's anti-apoptotic effect.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, we confirmed that PCF could protect HaCaT cells from UVB-induced apoptosis, which is consistent with our previous findings [9]. Furthermore, we investigated iNOS and TGF-b1 as molecular mechanism of UVBinduced apoptosis cells and PCF's anti-apoptotic effect.…”
Section: Discussionsupporting
confidence: 94%
“…The 879-Da octapeptide, consists of Pro, Asn, Ser, Thr, Arg, Hyl, Cys, and Gly, is developed by Yellow Sea Fisheries Research Institute Chinese Academy of Fishery Sciences. Previous studies in our lab revealed that PCF could inhibit UV-induced cell apoptosis [9], with the potential mechanism involves nitric oxide (NO) producing enzymes and NO levels [10,11]. However, many still remain unknown for PCF's antiapoptotic effect in cells exposed to UVB.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that UVB irradiation induced phosphorylation of JNK and inhibition of JNK significantly protected against UVB‐induced apoptosis 20 . In addition, the reactive oxygen species–JNK–caspase‐3 apoptosis cascade pathway is the main signalling pathway of HaCaT cell apoptosis induced by UVA and UVB 21 . The activation of the JNK pathway leads to the upregulation of the expression of cleaved caspase‐3 in HaCaT cells irradiated by UVA and UVB.…”
Section: Discussionmentioning
confidence: 99%
“…By centrifugation the supernatant was removed and 100 ml dimethyl sulfoxide (DMSO) was added. 10 min later, the absorbance was read at 570 nm in a microplate reader (Tecan Group Ltd, CH-8708 Männedorf, Switzerland) (Gao X et al 2001, Gao MQ et al 2007). …”
Section: Survival Of Cells Determination By Mttmentioning
confidence: 99%